Cortical Auditory Evoked Potentials in Response to Frequency Changes with Varied Magnitude, Rate, and Direction - Vonck, Bernard M.D. (J Assoc Res Otolaryngol, 2019)
Recent literature on cortical auditory evoked potentials has focused on correlations with hearing performance with the aim to develop an objective clinical tool. However, cortical responses depend on the type of stimulus and choice of stimulus parameters. This study investigates cortical auditory evoked potentials to sound changes, so-called acoustic change complexes (ACC), and the effects of varying three stimulus parameters. In twelve normal-hearing subjects, ACC waveforms were evoked by presenting frequency changes with varying magnitude, rate, and direction. The N1 amplitude and latency were strongly affected by magnitude, which is known from the literature. Importantly, both of these N1 variables were also significantly affected by both rate and direction of the frequency change. Larger and earlier N1 peaks were evoked by increasing the magnitude and rate of the frequency change and with downward rather than upward direction of the frequency change. The P2 amplitude increased with magnitude and depended, to a lesser extent, on rate of the frequency change while direction had no effect on this peak. The N1–P2 interval was not affected by any of the stimulus parameters. In conclusion, the ACC is most strongly affected by magnitude and also substantially by rate and direction of the change. These stimulus dependencies should be considered in choosing stimuli for ACCs as objective clinical measure of hearing performance.